Biology of xenogeneic cell and organ transplantation – from bench to bedside – the new German research foundation (DFG) transregio collaborative research centre for the next 4 (ultimately 12) years. (5th February 2013) - Reichart, Bruno
<x xml:space="preserve">Abstract</x> Discordant xenotransplantation research started in Hanover/Mariensee and in Munich in the late nineties – the latter receiving a substantial grant from the Bavarian Research Foundation. In 2003 both groups were invited by the German Research Foundation (DFG) to make a joint application to further develop xenotransplantation technology. This was peer‐reviewed, approved and continued with considerable success from 2004 to 2012. The Paul‐Ehrlich and Robert‐Koch Institutes, the official bodies responsible for microbiological safety in Germany, were subsequently included. Our unique interdisciplinary consortium combines basic scientists, animal biotechnologists and clinicians demonstrating an excellent co‐operation over the last 8 years. The tool box available to us includes pigs transgenic for human thrombomodulin, hemoxygenase‐1, A20, LEA 29Y, HLA‐E and TRAIL; key enabling technologies include gene targeting, large transgene vectors, transposon mediated transgenesis, zinc finger and TALE nuclease mediated gene targeting. In July 2012 our new Collaborative Research Centre (again supported by the DFG) commenced, continuing in the first instance to 2016 and ultimately until 2024. The strong Diabetes group at the University of Dresden, which currently runs the only successful allogeneic pancreatic islet transplantation in Germany, has now been incorporated. Our main goal is to translate preclinical studies into benefits for patients as quickly as possible. The consortium focuses on islet, cardiac and renal xenotransplantation; new biological heart valves for paediatric cases and young adults will be developed. Our endeavours will be supported by two ethicists to ensure best practice and promote public dialogue.